OPTINOFA—Intelligent assistance service for structured assessment in the emergency department OPTINOFA – Intelligenter Assistenzdienst zur strukturierten Ersteinschätzung in der Notaufnahme - Nyoungui, Elisabeth; Karg, Marina V.; Wieckenberg, Marc; Esslinger, Katrin; Schmucker, Michael; Reiswich, Andreas; Antweiler, Kai L.; Friede, Tim; Haag, Martin; Dormann, Harald; Blaschke, Sabine (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2024)
Background: Case numbers in central emergency departments (EDs) have risen during the past decade in Germany, leading to recurrent overcrowding, increased risks in emergency care, and elevated costs. Particularly the fraction of outpatient emergency treatments has increased disproportionately. Within the framework of the Optimization of emergency care by structured triage with intelligent assistant service (OPTINOFA, Förderkennzeichen [FKZ] 01NVF17035) project, an intelligent assistance service was developed. Patients and methods: New triage algorithms were developed for the 20 most frequent leading symptoms on the basis of established triage systems (emergency severity index, ESI; Manchester triage system, MTS) and provided as web-based intelligent assistance services on mobile devices. To evaluate the validity, reliability, and safety of the new OPTINOFA triage instrument, a pilot study was conducted in three EDs after ethics committee approval. Results: In the pilot study, n = 718 ED patients were included (age 59.1 ± 22 years; 349 male, 369 female). With respect to disposition (out-/inpatient), a sensitivity of 91.1% and a specificity of 40.7%, and a good correlation with the OPTINOFA triage levels were detected (Spearman’s rank correlation ρ = 0.41). Furthermore, the area under the curve (AUC) for prediction of disposition according to the OPTINOFA triage level was 0.73. The in-hospital mortality rate of OPTINOFA triage levels 4 and 5 was 0%. The association between the length of ED stay and the OPTINOFA triage level was shown to be significant (p < 0.001). Conclusion: The results of the pilot study demonstrate the safety and validity of the new triage system OPTINOFA. By definition of both urgency and emergency care level, new customized perspectives for load reduction in German EDs via a closer cooperation between out- and inpatient sectors of emergency care could be established.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Algorithm; Decision support techniques; Emergency medicine; Organizational decision-making; Triage